2020
DOI: 10.1080/00343404.2020.1826039
|View full text |Cite
|
Sign up to set email alerts
|

UK analysts’ and policy-makers’ perspectives on Brexit: challenges, priorities and opportunities for subnational areas

Abstract: This paper explores the perspectives of expert analysts and policy-makers on the implications of Brexit for different parts of the UK economy. For local and regional areas, the need for such expert voices to be heard is urgent, given the fact that UK subnational and substate governance authorities have been effectively blocked out of all Brexit-related negotiations, and as such, are wholly unprepared for the post-Brexit realities. The issues discussed in this paper reflect the key themes that came out of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The 'geography of discontent' refers to relationship between the geography of the anti-system voting patterns and the economic geography of productivity patterns. Several studies (see, e.g., Billing et al, 2019Billing et al, , 2021Los et al, 2017;McCann, 2016McCann, , 2018McCann, , 2020Rehák et al, 2021;Rodríguez-Pose, 2018) revealed that political responses and actions are shaped by regional development problems and a local community's own understanding of its perceived status and value in society. This understanding is formed by the relative economic performance and the degree to which a community and its individual citizens feel valued or exploited by the wider society.…”
Section: The Role Of Policy and Agencymentioning
confidence: 99%
“…The 'geography of discontent' refers to relationship between the geography of the anti-system voting patterns and the economic geography of productivity patterns. Several studies (see, e.g., Billing et al, 2019Billing et al, , 2021Los et al, 2017;McCann, 2016McCann, , 2018McCann, , 2020Rehák et al, 2021;Rodríguez-Pose, 2018) revealed that political responses and actions are shaped by regional development problems and a local community's own understanding of its perceived status and value in society. This understanding is formed by the relative economic performance and the degree to which a community and its individual citizens feel valued or exploited by the wider society.…”
Section: The Role Of Policy and Agencymentioning
confidence: 99%
“…This decision at a stroke made England by far the most centralized and top-down part of the whole EU regional funding arena covering some 500 million people. Out of the more than 250 NUTS-2 regional managing authorities for the EU Cohesion Policy funding programmes (McCann, 2015), England was more than five times the size of the next largest managing authority (Billing et al, 2021). A top-down centralization of this form and magnitude went both conceptually and operationally entirely against all of the post-2014 place-based reforms to EU Cohesion Policy originally set in train by the Barca (2009) report (Billing et al, 2021) and in the opposite direction to almost every other EU member state.…”
Section: Future Challenges and Opportunities: Devolution And A 'Shared Prosperity Fund'mentioning
confidence: 99%
“…Out of the more than 250 NUTS-2 regional managing authorities for the EU Cohesion Policy funding programmes (McCann, 2015), England was more than five times the size of the next largest managing authority (Billing et al, 2021). A top-down centralization of this form and magnitude went both conceptually and operationally entirely against all of the post-2014 place-based reforms to EU Cohesion Policy originally set in train by the Barca (2009) report (Billing et al, 2021) and in the opposite direction to almost every other EU member state. The subsidiarity principles of devolved shared management were almost entirely overturned within the UK, in many ways returning the application of EU regional funds within the UK policy to something like a pre-1989 logic (McCann, 2015).…”
Section: Future Challenges and Opportunities: Devolution And A 'Shared Prosperity Fund'mentioning
confidence: 99%
“…Repeatedly, institutional issues and questions of territorial governancelocal regional and devolved -were identified as enduring problems, originating long before the Brexit referendum. Billing et al (2021Billing et al ( , in this issue, p. 1574) argue that: local and regional development policy in the UK during the last decade has been very ad hoc and fragmented … [an] increasingly characterized by a rather ad hoc patchwork of different development geographies [which] … either overlap or fail to dovetail neatly with one another. The UK's devolved nations/jurisdictions are, the analysis suggests, generally better able to develop specific territorial responses to Brexit, particularly in Scotland.…”
Section: The Articlesmentioning
confidence: 99%